ANALISIS EFEKTIVITAS PAJAK DAERAH DAN FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP BESARNYA PENDAPATAN PAJAK DAERAH (STUDI KASUS KABUPATEN SUKOHARJO TAHUN 2012-2019) - Erniyawati Mustaqomah; Sri Hutami (Riset Manajemen dan Akuntansi, 2020)
Local tax is contributing the higest rrevenue to Local Genuine Income (PAD). Government attempt to increases local tax collection to improve PAD, especially through tax post. Establishing the effectiveness and factors that influencing the revenue from tax post begin a material subject. The Objective of this research is to measure degree of effectiveness and understanding the influence of inflation rate and Gross Regional Domestic Product on local tax revenue in Sukoharjo District from the Official of local revenue and the statistic Bureu (BPS) in Sukoharjo District. The literature study is conducted to support data collection. Result of this research indicates that the effectiveness of local tax collection in Sukoharjo District in period 2012-2019 is entirely very effective. Tax revenue in Sukoharjo District are most influenced by Gros Regional Domestic Product (PDRB). Based from these result, it may be suggested that the local government of Sukoharjo District in determining local tax shall firstly socialize the importance of tax for the development such taxpayer will be aware of paying tax in exchange for their welfare.